COlchicine to Prevent PeriprocEdural Myocardial Injury in Percutaneous Coronary Intervention (COPE-PCI): Coronary Microvascular Physiology Pilot Substudy. (29th May 2022) - Cole, Justin; Htun, Nay; Lew, Robert; Freilich, Mark; Quinn, Stephen; Layland, Jamie
Abstract : Aim . In this randomized pilot trial, we aimed to assess the anti-inflammatory effect of preprocedural colchicine on coronary microvascular physiology measurements before and after PCI. Methods . Patients undergoing PCI for stable angina (SA) or non-ST-elevation myocardial infarction (NSTEMI) were randomized to oral colchicine or placebo, 6- to 24-hours before the procedure. Strict prespecified inclusion/exclusion criteria were set to ensure all patients were given the study medication, had a PCI, and had pre- and post-PCI culprit vessel invasive coronary physiology measurements. Fractional flow reserve (FFR), Index of Microvascular Resistance (IMR), Coronary Flow Reserve (CFR), and Resistive Reserve Ratio (RRR) were measured immediately before and after PCI. CMVD was defined as any one of post-PCI IMR >32 or CFR <2 or RRR <2. High-sensitive-(hs)-troponin-I, hsCRP, and leucocyte count were measured before and 24 hours after PCI. Results . A total of 50 patients were randomized and met the strict prespecified inclusion/exclusion criteria: 24-colchicine and 26-placebo. Pre-PCI coronary physiology measurements, hs-troponin-I, and hsCRP were similar between groups. Although numerically lower in patients given colchicine, the proportion of patients who developed CMVD was not significantly different between groups (colchicine: 10 (42%) vs placebo: 16 (62%), p = 0.16 ). Colchicine patients had higher post-PCI CFR and RRR vs placebo (respectively: 3.25 vs 2.00, p = 0.03 & 4.25 vs 2.75, p < 0.01 ). Neutrophil count was lower after PCI in the colchicine arm p = 0.02, and hsCRP post-PCI remained low in both treatment arms (1.0 mg/L vs 1.7 mg/L, p = 0.97 ). Patients randomized to colchicine had significantly less PCI-related absolute hs-troponin-I change (46 ng/L vs 152 ng/L, p = 0.01 ). Conclusion . In this pilot randomized substudy, colchicine given 6 to 24 hours before PCI did not statistically impact the post-PCI CMVD definition used in this study, yet it did improve post-PCI RRR and CFR measurements, with less procedure-related troponin release and less inflammation.